PERAN PENDIDIKAN PANCASILA DALAM IMPLEMENTASI PENDIDIKAN KARAKTER DI ERA 4.0 - Sartika, Rinny; Ndona, Jacobus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the era of Industrial Revolution 4.0, technology and digitalization present new challenges for education, especially in shaping the character of the younger generation. Pancasila-based character education is very important so that the younger generation has intellectual intelligence and strong moral values. Pancasila, with values ​​such as divinity, humanity, unity, democracy and social justice, needs to be integrated into the curriculum and daily practice, including through digital media. In this way, it is hoped that students can understand and apply Pancasila values ​​in life, so that they are able to face modernization without losing national identity. The qualitative research method is based on literature studies which examine various sources regarding the role of Pancasila education in the implementation of education in the 4.0 era where the author collects data and information in the form of relevant journals, documents, dialogue books, magazines, articles, etc. The expected results in Pancasila-based character education are expected to produce a young generation who is not only academically intelligent but also has good morals and ethics, ready to face the challenges of globalization and technological developments without losing national identity.